Effect of soaking time on phase formation and electrical properties of PLZT based ceramics - Ladapak Chumprasert (2018)
Lead lanthanum zirconate titanate ceramics (PLZT) are well known for their excellent dielectric, piezoelectric and ferroelectric properties and electro-optic characteristics. The solid solutions of compounds are expected to possess very interesting properties, making them promising candidates for electromechanical devices. This study describes processing and sintering conditions and electrical properties of the PLZT ceramics (9/65/35) that were successfully prepared from the respective starting materials by vibro-milling mixed-oxide method at various soaking time conditions for optimized properties. A composition and microstructure of the ceramics were investigated using X-ray diffraction and scanning electron microscopy. The dielectric properties of the densified samples were examined as a function of temperature and frequency to verify the relationships between soaking time conditions, phase formation, densification, microstructural development, dielectric, and ferroelectric characteristics. © 2013 Copyright Taylor and Francis Group, LLC.